SAT0289 Serum Soluble HLA E: A Biomarker of Disease Activity and Coronary Arteritis in Takayasu Arteritis. (10th June 2014) - Goel, R.; Mohan, H.; Kabeerdoss, J.; Jayaseelan, V.; Jude, J.; Joseph, G.; Danda, D.
Abstract : Background: Takayasu Arteritis (TA) is a large vessel vasculitis with narrowing or ectasia of aorta or its branches as a sequel. Lack of ideal blood biomarkers renders disease activity assessment difficult. Imaging is the only way to assess coronary artery involvement accounting for 10-15% of TA (1). HLAE polymorphisms are shown to be associated with coronary artery aneurysms in Kawasaki disease. Objectives: To explore the utility of sHLAE as a marker of disease activity and coronary involvement in TA. Methods: sHLAE was measured by ELISA in sera of 39 patients satisfying ACR 1990 classification criteria for TA, attending our institution and in 13 healthy subjects. Active disease was defined as Indian Takayasu Arteritis score 2010 (ITAS 2010) ≥1 with/without raised inflammatory markers or angiographic evidence of active disease (2). sHLAE levels are depicted as median with inter-quartile range (IQR). Non parametric tests were used for comparing sHLAE levels of patients with active TA, stable TA and healthy controls and those with or without coronary involvement. Confidence interval (CI) was determined using boot strap. Results: Among 39 patients (mean age: 31±12 years, disease duration: 39±44.5 months, male:female::4:35), 23 had active disease (ITAS =10 (3-14); CRP 12.3 (8.5-21 mg/L); ESR 51 (33-75) mm/1st hr; median, (IQR)) while 16 had stable disease (ITAS =0 (0); CRP 0.95 (0.4-5.8) mg/L; ESR 16 (8-21) mm/1st hr; median (IQR)). At baseline visit, sHLAE concentration was 37.6 (IQR: 19.7-63.5) pg/ml in patients with active TA which was significantly higher than those with stable disease (13.01 (IQR: 8.5- 24.9) pg/ml; 95% CI: 5.7 -39.6; p =0.026) but was not statistically different from that in healthy controls (37.6 (IQR: 19.7-63.5) vs 26.5 (IQR: 3.37-35) pg/ml; 95% CI: -6.7 to 37.0; p=0.15). sHLAE concentrations at follow up visit after treatment, measured for 17 patients (10 active and 7 stable) were not different between active and inactive group (36.2 (IQR: 22-52) vs 28.2 (IQR: 12.2- 28.8) pg/ml; p=0.17). Among 39 patients, 5 had coronary involvement. Median sHLAE concentration in patients with coronary involvement was 51.3 (IQR: 44.8- 69.7) pg/ml, which was significantly higher than 19.8 (IQR: 9.3-38.6) pg/ml in those without coronaries involved ( p =0.01). Receiver-operating-characteristic (ROC) curve computed an area under curve of 0.847 (95% CI: 0.72-0.97). The cutoff level of sHLAE which indicated coronary involvement with sensitivity of 80% and specificity of 80.4% was estimated to be 44.8 pg/ml . Conclusions: sHLAE levels in serum could differentiate active from stable disease in our cohort of TA patients at baseline visit. sHLAE levels was a good biomarker of coronary artery involvement in TA. Larger studies are needed to validate these observations. References: Matsubara O, Kuwata T, Nemoto T, Kasuga T, Numano F. Coronary artery lesions in Takayasu arteritis: pathological considerations. Heart Vessels Suppl. 1992;7:26–31. Misra R, Danda D, Rajappa SM, Ghosh A, Gupta R, Mahendranath KM, et al. Development and initial validation of the Indian Takayasu Clinical Activity Score (ITAS2010). Rheumatol Oxf Engl. 2013 Oct;52(10):1795–801. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4843